Understanding the Hedonic Consumption of Servicescapes: The Case of LEGOLAND - Mazhar, Muhammad Haider (2015)
This study is based on the concept of hedonic consumption and the importance of servicescapes. The study applied a qualitative approach in understanding the hedonic aspects and the experiences with servicescape setting in LEGOLAND, Windsor UK. The data was collected through autoethnography and interviews. The results indicated “Fun for children” and “learning” as the primary factors of motivations for parents. The Role Projection behaviour of kids was also reported on the bases of observatory data. For the experiential aspects “live shows” at park and “theming” were reported as most influential factors